A green and sustainable organic molecule electrode prepared by fluorenone for more efficient energy storage. (1st May 2021) - Lv, Liwen; Hu, Zhongai; An, Ning; Xie, Kefeng; Yang, Yuying; Zhang, Ziyu; Li, Zhimin
Highlights: A fluorenone molecule electrode was reported, in which DHFO was anchored on GO to form hierarchical porous hydrogel. The redox peak position of DHFO/rGO is located near 0.75 V, which is suitable for positive electrode in EES. An ASC was assembled and delivered high energy density (28.57 Wh Kg −1 ), finally lighted 45 LED bulbs. Abstract: Here, we report an organic molecule electrode for more efficient energy storage, in which 2, 7-Dihydroxy-9-fluorenone (DHFO) molecules are anchored on interconnected and highly conductive graphene sheets by non-covalent π–π interactions. The optimal DHFO/rGO composite can reach a high specific capacitance of 412.3 F g −1 at scan rate of 5 mV s −1 in 1 mol L −1 H2 SO4 aqueous electrolyte with a satisfactory capacitive retention of 91% after 10, 000 consecutive constant galvanostatic charge-discharge at current density of 5 A g −1 . And it is worth noting that the Faraday current response peaks occurs within the positive potential range around 0.75 V, which is more suitable for positive electrode materials of supercapacitors with high performances. Additionally, charge storage mechanism and binding interactions of DHFO on graphene was evaluated based on the density functional theory (DFT) calculations. To match with the consequent positive electrode, AQ functionalized graphene (AQ/rGO) was prepared as negative electrode. Benefiting from the companionable match of two electrodes in structure, charge quantity and kinetics, the as-assembled asymmetrical supercapacitor (DHFO/rGO//AQ/rGO) delivers a maximum energy density of 28.57 Wh kg −1 along with 0.62 kW kg −1, and excellent cycle stability (82.3% specific capacitance retention after 10, 000 cycling at 5 A g −1 ). Two tandem DHFO/rGO//AQ/rGO devices could light 45 LEDs. Graphical abstract: Image, graphical abstract